Order and disorder in NMC layered materials: a FAULTS simulation analysis. (6th February 2017) - Reynaud, Marine; Casas-Cabanas, Montse
Abstract : The program FAULTS has been used to simulate the X-ray powder diffraction (XRD), neutron powder diffraction (NPD), and electron diffraction (ED) patterns of several structural models for LiNi1/3 Mn1/3 Co1/3 O2, including different types of ordering of the transition metal (TM) cations in the TM slabs, different amounts of Li + /Ni II+ cation mixing and different amounts of stacking faults. The results demonstrate the relevance of the structural information provided by NPD and ED data as compared with XRD to characterize the microstructure of NMC (LiNi1− y-z Mn y Co z O2 ) compounds.